Electron and photon efficiencies in LHC Run 2 with the ATLAS experiment - Aad, G.; Åkesson, T.P.A. ; 0000-0003-4141-5408; Doglioni, C.; Ekman, P.A. ; 0000-0002-7032-2799; Hedberg, V.; Herde, H. ; 0000-0001-8926-6734; Konya, B.; Lytken, E. ; 0000-0002-8141-3995; Poettgen, R. ; 0000-0002-3304-0987; Simpson, N.D.; Smirnova, O. ; 0000-0003-2517-531X; Zwalinski, L. (Journal of High Energy Physics, 2024)
Precision measurements of electron reconstruction, identification, and isolation efficiencies and photon identification efficiencies are presented. They use the full Run 2 data sample collected by the ATLAS experiment in pp collisions at a centre-of-mass energy of 13 TeV during the years 2015–2018, corresponding to an integrated luminosity of 139 fb−1. The measured electron identification efficiencies have uncertainties that are around 30%–50% smaller than the previous Run 2 results due to an improved methodology and the inclusion of more data. A better pile-up subtraction method leads to electron isolation efficiencies that are more independent of the amount of pile-up activity. Updated photon identification efficiencies are also presented, using the full Run 2 data. When compared to the previous measurement, a 30%–40% smaller uncertainty is observed on the photon identification efficiencies, thanks to the increased amount of available data. © The Author(s) 2024.
Keywords: Hadron-Hadron Scattering